The substitution of the President of the Republic of Italy in the light of constitutional regulations and political practice - Witkowski, Zbigniew; Jachimowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The authors analyse the problem of the nature of the substitution of the President of the Republic of Italy. This issue is loosely regulated in the Italian Constitution and for this reason there are some practical doubts in interpretation. President’s permanent incapacity is not specifically defined by the constitutional provisions and that is why in some cases it is difficult to duly ascertain and declare the permanent incapacity. Should the President be unable to perform his duties, they shall be carried out by the Speaker of the Senate, however powers and duties of the Speaker are not defined. The authors argue that the Italian doctrine of constitutional law has significantly improved regulatory framework and the legal practice.